2004
DOI: 10.1631/jzus.2004.1239
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 treated murine dendritic cells are maturation resistant and down-regulate Toll-like receptor 4 expression

Abstract: Abstract:Objective: To explore the effects of transforming growth factor β1 (TGF-β1) on dendritic cells (DC). Methods: Murine bone marrow cells were cultured with GM-CSF and TGF-β1 to develop TGF-β1-treated DC (TGFβ-DC). Then they were stimulated by lipopolysaccharide (LPS). Their phenotypes were assessed by flow cytometry (FCM). The allogeneic stimulating capacity of DC was measured by mixed lymphocyte reaction (MLR) using BrdU ELISA method and IL-12p70 protein was detected by ELISA. The expression of Toll-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 13 publications
1
15
1
2
Order By: Relevance
“…In this study, we showed that PMN-Ect inhibited the maturation of iMoDCs by LPS and induced new morphological and functional characteristics with a resulting reduced capacity to activate T cells. In addition, iMoDCs exposed to PMN-Ect released TGF-␤1 and it might well be that to some or a larger extent TGF-␤1 was responsible for the down-regulation of TLR4-mediated maturation of iDCs, as observed by others (15,34), and of surface expression of CCR7 (29). During DC maturation, the upregulated CCR7 is responsible for directing the migration of DCs to the lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed that PMN-Ect inhibited the maturation of iMoDCs by LPS and induced new morphological and functional characteristics with a resulting reduced capacity to activate T cells. In addition, iMoDCs exposed to PMN-Ect released TGF-␤1 and it might well be that to some or a larger extent TGF-␤1 was responsible for the down-regulation of TLR4-mediated maturation of iDCs, as observed by others (15,34), and of surface expression of CCR7 (29). During DC maturation, the upregulated CCR7 is responsible for directing the migration of DCs to the lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, transforming growth factor-beta (TGF-beta) is a cytokine expressed during lung development and is important for epithelial differentiation and maturation needed for surfactant synthesis [30]. Recent evidence indicates TGF-beta may also inversely regulate TLR4 expression [31,32]. The net effect may be promotion of epithelial surfactant synthesis while minimizing inflammation that could complicate respiratory function in the neonate.…”
Section: Discussionmentioning
confidence: 99%
“…Mou et al 44 observed that in vitro treatment of murine bone marrow-derived dendritic cells with TGF-β1 resulted in decreased expression of TLR4. This finding correlated with reduced sensitivity to lipopolysaccharide-induced maturation.…”
Section: Immunoregulation Of Dendritic Cells By Il-10mentioning
confidence: 99%